Safety, Efficacy and Prognostic Benefit of Atrial Fibrillation Ablation in Heart Failure with Preserved Ejection Fraction - Nicolas Johner; Mehdi Namdar; Dipen C Shah (Arrhythmia & Electrophysiology Review)
Up to 65% of patients with heart failure with preserved ejection fraction (HFpEF) develop AF during the course of the disease. This occurrence is associated with adverse outcomes, including pump failure death. Because AF and HFpEF are mutually reinforcing risk factors, sinus rhythm restoration may represent a disease-modifying intervention. While catheter ablation exhibits acceptable safety and efficacy profiles, no randomised trials have compared AF ablation with medical management in HFpEF. However, catheter ablation has been reported to result in lower natriuretic peptides, lower filling pressures, greater peak cardiac output and improved functional capacity in HFpEF. There is growing evidence that catheter ablation may reduce HFpEF severity, hospitalisation and mortality compared to medical management. Based on indirect evidence, early catheter ablation and minimally extensive atrial injury should be favoured. Hence, individualised ablation strategies stratified by stepwise substrate inducibility provide a logical basis for catheter-based rhythm control in this heterogenous population. Randomised trials are needed for definitive evidence-based guidelines.